PEMBIAYAAN MUDHARABAH DAN DAMPAKNYA TERHADAP OMSET USAHA MIKRO DI KOPERASI SIMPAN PINJAM PEMBIAYAAN SYARIAH EL-UMMA - TAMI NADIRAH; DENI LUBIS; ALLA ASMARA (Prodi Manaj. Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam – UIN Imam Bonjol Padang, 2019)
Micro Enterprise Sector is a sector that has an important role in the economy of the country. However the number of problems still felt by the sector, one of them is the problem of capital. Mudharabah ﬁnancing can be an alternative for micro businesses to resolve the problem. KSPPS El-Umma is one of the institution that oﬀer Mudharabah ﬁnancing for micro business actors in developing their business. This study aims to analyze the eﬀectiveness of mudharabah ﬁnancing and its impact on business turnover. The method that used in this research is descriptive analysis method using Likert scale to measure the eﬀectiveness level of ﬁnancing disbursed and to describe the impact of ﬁnancing on business development also using Ordinary Least Square (OLS) method to determine the factors that inﬂuence the business turnover. The result of analysis with Likert scale as a whole mudharabah ﬁnancing distributed by KSPPS has been classiﬁed as eﬀective, and there is business development after getting ﬁnancing seen from the increase of business turnover. The Factors that inﬂuencing the turnover of business are the length of business, age, the amount of ﬁnancing and the term of ﬁnancing.